Food poverty and youth work – A community response. (February 2022) - Ord, Jon; Monks, Annie
This article discusses the findings of a small-scale study investigating the impact of food poverty on youth work in community based open access settings. It documents the growing impact of food poverty on the role of youth work in deprived communities and explores the role youth workers play in addressing it. Firstly this 'community response' addresses the issue of food poverty in localities where it arises. However, it not only meets basic needs, but it also helps build social capital by enacting important social relationships associated with food by 'eating together'. Such responses also have the potential to combat stigma and abjection through the creation of critical consciousness and political education. The research also highlights the need for greater coordination of this response and for youth centres to be less isolated from other services. Finally, the legacy of food policy within youth work is highlighted, previously dominated by a focus on healthy eating since Every Child Matters (2003). Post austerity, for many communities the concern is simply 'eating'!